AS DIFERENTES ESFERAS SÓCIO-DISCURSIVAS COMO CRITÉRIO PARA A ELABORAÇÃO DE CURRÍCULOS - Rodrigues, Rosângela Hammes (Intercâmbio, 2010)
The purpose of this work is to discuss a topic concerning to the different social circles of discursive activity as a possible criterion in view of elaboration and settlement of curricular progression of the Portuguese language contents, to be set up from discursive genders.